2014
DOI: 10.1158/1055-9965.epi-13-0181
|View full text |Cite
|
Sign up to set email alerts
|

Association of Marijuana Smoking with Oropharyngeal and Oral Tongue Cancers: Pooled Analysis from the INHANCE Consortium

Abstract: Background The incidence of oropharyngeal and oral tongue cancers have increased over the last twenty years which parallels increased use of marijuana among individuals born after 1950. Methods Pooled analysis of individual-level data from nine case-control studies from the U.S. and Latin America in the INHANCE consortium. Self-reported information on marijuana smoking, demographic, and behavioral factors was obtained from 1,921 oropharyngeal cases, 356 oral tongue cases, and 7,639 controls. Results Compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 45 publications
6
57
0
1
Order By: Relevance
“…Socioeconomic status is influential in oral cancer (Moles et al, 2008). Many other factors are possibly implicated in mouth, lip and oropharyngeal cancers, including immunosuppression (van Leeuwen et al, 2009), familial and genetic factors (Turati et al, 2013), diet (Garavello et al, 2009), marijuana use (Marks et al, 2014), and even exercise (Nicolotti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status is influential in oral cancer (Moles et al, 2008). Many other factors are possibly implicated in mouth, lip and oropharyngeal cancers, including immunosuppression (van Leeuwen et al, 2009), familial and genetic factors (Turati et al, 2013), diet (Garavello et al, 2009), marijuana use (Marks et al, 2014), and even exercise (Nicolotti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis included 9 case-control studies from Baltimore, Seattle (407 cases and 615 controls)(13), Latin America, Boston (434 cases and 547 controls)(20), Los Angeles (493 cases and 1,040 controls)(16), and North Carolina, that recruited subjects from 1985 to 2013 (21). The previous INHANCE report (19) had included 5 of these case-control studies; thus 765 of the 1,921 oropharyngeal cancer cases and 211 of the 356 oral tongue cases had been included in the previous analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the duration of illicit drug use was even less than of legal drugs, it is likely that the absence of lesions is due to the short duration of illicit drug use in our sample. Carvalho et al 30 found no association between lifetime marijuana use and the risk for development of oral cancer, while Marks et al 5 suggested that the association of marijuana use with head and neck carcinoma may differ by tumor site. Because of the scarcity of studies and variations between them, it is difficult to define the relationship between amount of marijuana smoked and the appearance of mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Moreover, users are more prone to oral infections, possibly due to alterations in oral immunology, 2 and drug use can be associated with dysplastic changes and potentially malignant disorders of the oral mucosa, increasing the incidence of squamous cell carcinoma. 5 Marijuana cigarettes can contain up to twice the amount of polycyclic aromatic hydrocarbons as tobacco cigarettes, and the usual consumption without a filter leads to a higher concentration of inhaled smoke. However, the relationship between marijuana use and oral cancer is still not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation